2011
DOI: 10.1080/19440049.2011.608382
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of marine lipophilic toxins in mussels, oysters and cockles using liquid chromatography-mass spectrometry: inter-laboratory validation study

Abstract: Thirteen laboratories participated in an interlaboratory study to evaluate the method performance characteristics of a liquid chromatography tandem mass spectrometric method (LC-MS/MS) for marine lipophilic shellfish toxins. Method performance characteristics were evaluated for mussel (Mytilus edulis), oyster (Crassostrea gigas) and cockle (Cerastoderma edule) matrices. The specific toxin analogues tested included okadaic acid (OA), dinophysistoxins-1 and-2 (DTX1,-2), azaspiracids-1,-2 and-3 (AZA1,-2,-3), pect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Indeed, lower LoDs were expected for PTX2 in mussel compared to passive sampler, as the mussel matrix caused ion enhancement for PTX2. This was not the case, perhaps reflecting the high level of variability previously associated with this toxin [6,13]. With regard to regulatory levels for toxins, satisfactory detection limits were obtained on both low and high resolution mass spectrometers for methanol, mussel and SPATT matrices.…”
Section: Accuracy and Detection Limitsmentioning
confidence: 74%
See 1 more Smart Citation
“…Indeed, lower LoDs were expected for PTX2 in mussel compared to passive sampler, as the mussel matrix caused ion enhancement for PTX2. This was not the case, perhaps reflecting the high level of variability previously associated with this toxin [6,13]. With regard to regulatory levels for toxins, satisfactory detection limits were obtained on both low and high resolution mass spectrometers for methanol, mussel and SPATT matrices.…”
Section: Accuracy and Detection Limitsmentioning
confidence: 74%
“…To achieve this goal, different studies have developed and validated quantitative methods for the analysis of phycotoxins, typically using low resolution mass spectrometry (LRMS) [4][5][6][7][8][9]. This technique is now being increasingly used for monitoring [10,11] and for characterization of reference materials [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, okadaic acid is associated with chronic diseases such as tumor production and cancer. Okadaic acid is a marine biotoxin produced by dinoflagellates and it accumulates in various host tissues including shellfish and sponges [175,176,177]. It is a tumor promoter and potent inhibitor of PP1/2A.…”
Section: Mechanisms Of Toxicitymentioning
confidence: 99%
“…2074/2005. A number of alternative methods have already been proposed for the detection of OA and derivatives including liquid chromatography-mass spectrometry (LC-MS)-based analysis, which inter-laboratory validation study demonstrated its suitability as alternative detection method ( Van den Top et al, 2011), and a colorimetric protein phosphatase 2A (PP2A) assay was also demonstrated suitable as alternative method (Smienk et al, 2012(Smienk et al, , 2013. Immunoassays have also been developed for the detection of OA, such as ELISA-based assay developed by Kreuzer et al (1999), which relied on commercial antibodies.…”
Section: Introductionmentioning
confidence: 99%